2022
DOI: 10.1080/19490976.2022.2046246
|View full text |Cite
|
Sign up to set email alerts
|

Lacticaseibacillus paracasei sh2020 induced antitumor immunity and synergized with anti-programmed cell death 1 to reduce tumor burden in mice

Abstract: The gut microbiota was emerging as critical regulatory elements in shaping the outcome of cancer immunotherapy. However, the underlying mechanisms by which the gut commensal species enhance antitumor immunity remain largely unexplored. Here, we show that the gut microbiota from healthy individuals conferred considerable sensitivity to anti-PD-1 in the colorectal cancer (CRC) tumor-bearing mice, whereas gut microbiota from CRC patients failed to do so. By 16S rRNA gene sequencing, we identified Lact… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(26 citation statements)
references
References 48 publications
0
26
0
Order By: Relevance
“…Currently, the gut microbiota has attracted the attention of researchers in terms of its role in antitumor immunotherapy ( Cremonesi et al, 2018 ; Zitvogel et al, 2018 ; Bouferraa et al, 2021 ; Matson et al, 2021 ; Xing et al, 2021 ). Researchers have adopted multiple mouse models or faecal microbiota transplantation (FMT) models to reveal the relationship between the gut microbiota and ICIs ( Sivan et al, 2015 ; Vétizou et al, 2015 ; Yi et al, 2018 ; Elkrief et al, 2019 ; Zhang et al, 2022 ). These studies suggest that both the commensal gut microbiota and that of healthy people play an important role in the immune microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the gut microbiota has attracted the attention of researchers in terms of its role in antitumor immunotherapy ( Cremonesi et al, 2018 ; Zitvogel et al, 2018 ; Bouferraa et al, 2021 ; Matson et al, 2021 ; Xing et al, 2021 ). Researchers have adopted multiple mouse models or faecal microbiota transplantation (FMT) models to reveal the relationship between the gut microbiota and ICIs ( Sivan et al, 2015 ; Vétizou et al, 2015 ; Yi et al, 2018 ; Elkrief et al, 2019 ; Zhang et al, 2022 ). These studies suggest that both the commensal gut microbiota and that of healthy people play an important role in the immune microenvironment.…”
Section: Introductionmentioning
confidence: 99%
“…The gut microbiota also has been demonstrated to enhance the therapeutic response to immune checkpoint inhibitors though targeting immunomodulatory molecules or their ligands on the surfaces of T cells ( McCulloch et al., 2022 ; Wu et al., 2022 ; Zhang et al., 2022 ; Zhao et al., 2022 ). The combination has been approved for treating various malignant tumors, including NAFLD-associated HCC ( Baruch et al., 2021 ; Davar et al., 2021 ; Shiraishi et al., 2022 ).…”
Section: Novel Strategy For Nafld Treatment Based On Gut Microbiotamentioning
confidence: 99%
“…L. paracasei sh2020–triggered antitumor immune response is dependent on CD8 + T cells. In vitro and in vivo studies have shown that the L. paracasei sh2020 enhanced CD8 + T-cell recruitment, with increased T-cell infiltration, and improved the poorly infiltrated TME, thus promoting immunotherapy ( Table 1 ) ( Zhang, et al, 2022 ). A probiotic mixture containing B. longum , B. bifidum , L. acidophilus , L. plantarum, and other components inhibits the invasion, migration, and proliferation of CT26 cells and may exert anti-tumor effects by inducing CD8 + T cell immune responses ( Table 1 ) ( Shang, et al, 2020 ).…”
Section: Microbes and The Tumor Microenvironmentmentioning
confidence: 99%
“…Lactobacillus paracasei sh2020 promotes the expression of T cell chemokines such as chemokine (C-X-C motif) ligand (CXCL)9, CXCL10, and CXCL11. In an in vitro tumor cell culture model, stimulation of L. paracasei sh2020 may lead to increased production of CXCL10, a T helper type 1 chemokine that controls the entry of major anti-tumor immune cells into tumor bed ( Table 1 ) ( Figure 1 ) ( Zhang, et al, 2022 ). Lactobacillus -derived exopolysaccharide-R1-induced T cells can infiltrate CCL20-producing tumors and produce IFN-γ, enhancing the effect of ICB therapy in producing CCL20 tumors in mice ( Table 1 ) ( Figure 1 ) ( Kawanabe-Matsuda, et al, 2022 ).…”
Section: Microbes and The Tumor Microenvironmentmentioning
confidence: 99%